TRANSFORMASI DAN INOVASI MANAJEMEN PENDIDIKAN ISLAM (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
In this era of global reform is necessary a renewal and improvement of the quality of society in order to ensure there will be many changes in society, both in terms of education, social and cultural rights are always evolving. The changes are a result of the development of science and technology is rapidly increasing, which in turn form the characteristic want competent people to beat each other. So there is no place in society without competition. Competition is the principle of a new life, because the world is open and Compete who can create something for the better. Transformation and innovation is needed at this time, it will bring a change and renewal in Islamic education management.